The Effectiveness of Using Blindfold Games to Improve Students’ Vocabulary - Fibri Indira Lisanty (BATARA DIDI : English Language Journal, 2022)
The main aim of the study is to examine the effectiveness of blindfold game to improve the students’ vocabulary mastery. The writer used random sampling technique to take the samples and total number of the sample were 20 students. The instrument of the study was vocabulary test. The result of the study reveals that there is a significant different between the students’ vocabulary mastery before and after using blindfold game. In the pre-test, there are 2 or 10% students get very poor, 7 or 35% students get poor, 8 or 55% students get fair and also 3 or 55% students get average classification. While in the post test, there are 8 or 40% students get average score, 11 or 55% students get good score, and only 1 or 15% students who get very good classification. The means score of the post-test is greater that pre-test (56.25 < 75. 90). The standard deviation of pre - test is 15. 18 and post-test is 9. 19. While P- Value = 0,000, (α)= 0,05. It means that the t - test is smaller than (α).